Analisis Akad Top Up E-Money dengan Pendekatan Fiqh - Muhammad Furqon Almurni; Tatang Hidayat; Nuradi Nuradi (Universitas Islam Negeri Alauddin Makassar, 2021)
The ever-evolving science and technology provide new innovations for the development of money. This development gave birth to electronic money which was widely used by the public. One of the causes of polemic towards e-money is how the fiqh ulama approach fiqh to top up e-money. Fiqh approach is very important for contemporary problems to punish a problem and its derivatives. The purpose of this study is to analyze how contemporary ulama approach fiqh towards the e-money top up contract. There are at least four fiqh approaches to top up e-money, namely al-Ijarah al-Maushufah fi Dzimmah, Wadi'ah, Qard, and Sharf. The method used in this research is a qualitative method with the type of library research. From the research results, it is found that the more appropriate fiqh approach when a customer top up e-money is the sharf contract, namely the exchange of currency with electronic money. With this approach, the discount given by the publisher to the customer is not usury but a gift that is allowed by syara 'as a promotional step for e-money issued by the publisher.